A COMPARATIVE STUDY OF DIALECTAL LEXEMES IN THE QASHQADARYO REGION AND THE UZBEK LITERARY LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines dialectal lexemes preserved in the dialects of the Qashqadaryo region and their reflection in the modern literary Uzbek language. Dialects are viewed as important sources of historical vocabulary that has become obsolete or stylistically limited in the standard language. The study employs descriptive, comparative, and historical-linguistic methods based on data from spoken dialectal speech, regional folklore texts, and Uzbek dialectological dictionaries. The findings show that Qashqadaryo dialects preserve numerous archaic lexemes, particularly in semantic fields related to traditional lifestyle and agriculture. Some lexemes retain their original meanings, while others undergo semantic change or lack literary equivalents. The research highlights the importance of dialectal studies for understanding the diachronic development of Uzbek vocabulary and preserving linguistic heritage.